Quantitative Profiling of Oxylipins in Acute Experimental Intracerebral Hemorrhage - Yuan, Jun-Jie; Chen, Qiong; Xiong, Xiao-Yi; Zhang, Qin; Xie, Qi; Huang, Jia-Cheng; Yang, Guo-Qiang; Gong, Chang-Xiong; Qiu, Zhong-Ming; Sang, Hong-Fei; Zi, Wen-Jie; He, Qian; et al. (Frontiers in Neuroscience, 2020)
Oxylipins are series of bioactive lipid metabolites derived from polyunsaturated fatty acids and involved with the maintenance of cerebral homeostasis and development of intracerebral hemorrhage (ICH). However, comprehensive quantification of the oxylipins profile in ICH remains unknown. Therefore, ICH mice were constructed and LC-MS/MS was then performed to quantify the change of oxylipins in ICH. The expression of oxylipins relative enzymes were also reanalyzed based on RNA-seq data from our constructed ICH dataset. A total of 58 oxylipins were quantifiable and 17 oxylipins were increased while none was decreased significantly in the first 3 days of ICH. most increased oxylipins in ICH were derived from AA (10/17) and EPA (4/17) followed by LA (2/17) and DHA (1/17). 18-HEPE from EPA was the only oxylipins that kept increased significantly from 0.5d to 3d following ICH. Furthermore, 14 of the increased oxylipins reached peaks at the first day of ICH, and soon decreased while 5 oxylipins (PGJ2, 15-oxo-ETE, 12-HEPE, 18-HEPE and 5-oxo-ETE) that were increased at 3d after ICH suggesting the profile shifted as the progression of ICH. In our constructed RNA-seq datasetbased on ICH mice, 90 oxylipins relative molecules were detected except for COX. Among them, Cyp4f18, Cyp1b1, Cyp2d3, Cyp2e1, Cyp1a1, ALOX5AP and PLA2g4a was found upregulated and Cyp26b1 was found to decrease in ICH. Besides, there was no significant change of sEH in ICH. This study provides fundamental data on the profile of oxylipins and their enzymes in ICH. We found that the profile shifted as the progression of ICH and the metabolism of AA and EPA was highly affected in ICH, which will help further studies exploring the functions of oxylipins in ICH.